EmrR-Dependent Upregulation of the Efflux Pump EmrCAB Contributes to Antibiotic Resistance in Chromobacterium violaceum - Barroso, Kelly C. M.; Previato-Mello, Maristela; Batista, Bianca B.; Batista, Juliana H.; da Silva Neto, José F. (Frontiers in Microbiology, 2018)
Chromobacterium violaceum is an environmental Gram-negative bacterium that causes infections in humans. Treatment of C. violaceum infections is difficult and little is known about the mechanisms of antibiotic resistance in this bacterium. In this work, we identified mutations in the MarR family transcription factor EmrR and in the protein GyrA as key determinants of quinolone resistance in C. violaceum, and we defined EmrR as a repressor of the MFS-type efflux pump EmrCAB. Null deletion of emrR caused increased resistance to nalidixic acid, but not to other quinolones or antibiotics of different classes. Moreover, the ΔemrR mutant showed decreased production of the purple pigment violacein. Importantly, we isolated C. violaceum spontaneous nalidixic acid-resistant mutants with a point mutation in the DNA-binding domain of EmrR (R92H), with antibiotic resistance profile similar to that of the ΔemrR mutant. Other spontaneous mutants with high MIC values for nalidixic acid and increased resistance to fluoroquinolones presented point mutations in the gene gyrA. Using DNA microarray, Northern blot and EMSA assays, we demonstrated that EmrR represses directly a few dozen genes, including the emrCAB operon and other genes related to transport, oxidative stress and virulence. This EmrR repression on emrCAB was relieved by salicylate. Although mutation of the C. violaceum emrCAB operon had no effect in antibiotic susceptibility or violacein production, deletion of emrCAB in an emrR mutant background restored antibiotic susceptibility and violacein production in the ΔemrR mutant. Using a biosensor reporter strain, we demonstrated that the lack of pigment production in ΔemrR correlates with the accumulation of quorum-sensing molecules in the cell supernatant of this mutant strain. Therefore, our data revealed that overexpression of the efflux pump EmrCAB via mutation and/or derepression of EmrR confers quinolone resistance and alters quorum-sensing signaling in C. violaceum, and that point mutation in emrR can contribute to emergence of antibiotic resistance in bacteria.